A Methodology for Modelling Preservation, Access and Sustainability. (10th August 2022) - Saunders, David
ABSTRACT: The interrelationship and interdependence between preservation, access and sustainability are explored, looking at the changing balance in their importance. The adoption of sustainability by cultural heritage organisations over the last 30 years is briefly traced, culminating in the United Nations' Sustainable Development Goals, before developing a simpler framework for considering the relationship between sustainability and the display and preservation of collections. Alongside environmental and economic criteria, this framework includes two people-centred considerations of sustainability – social and societal. The five 'pillars' in this model are completed by the concept of operational sustainability. By considering preservation as societal sustainability and access as social sustainability, the single conceptual model that also includes environmental, economic and operational sustainability can be used to assess the effect of specific policies and practices on overall organisational sustainability. To demonstrate its use, the model is applied to a number of scenarios typically encountered in cultural heritage institutions to explore their effect on the different categories of sustainability. The method is particularly effective and informative when considering how a change in practice might affect each type of sustainability, making it a useful tool in decision-making.